Citizen-consumers as change agents - Spaargaren, Gert (Ökologisches Wirtschaften - Fachzeitschrift, 2008)
Environmental change is not possible without the active involvement of key actors in civil society. For SCP policies to be successful, instru- ments and strategies for the greening of consumption practices have to be developed in correspondence with the lifestyle concerns of citizen-consumers.
Keywords: Sustainable Consumption; Production policies